2016
DOI: 10.1097/mca.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable vascular scaffolds

Abstract: In recent years, bioresorbable vascular scaffolds (BVS) have been introduced into clinical practice. The main advantage of BVS is that they overcome the problem of the foreign body in the treated artery. BVS, once placed into narrowed coronary vessels, behave like a conventional drug-eluting stent, but a device that disappears over time can preserve the anatomy and physiology of the treated vessel. The progression of stenosis after stenting has been attributed, at least in part, to inflammation around metallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A recent discussion on the emerging bioresorbable vascular scaffolds (BVS) is also noteworthy. 22 Compared with the conventional metal stents, BVS have many advantages, including the maintenance of the normal physiological and anatomic structure of the stented blood vessel, the significant decrease in inflammation compared to that caused by the use of conventional stents, and their eventual absorption and achievement of a normal vasomotor tone. Our future plan is to study how BVS affect the no-reflow phenomenon observed after the utilization of conventional stents and to elucidate the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent discussion on the emerging bioresorbable vascular scaffolds (BVS) is also noteworthy. 22 Compared with the conventional metal stents, BVS have many advantages, including the maintenance of the normal physiological and anatomic structure of the stented blood vessel, the significant decrease in inflammation compared to that caused by the use of conventional stents, and their eventual absorption and achievement of a normal vasomotor tone. Our future plan is to study how BVS affect the no-reflow phenomenon observed after the utilization of conventional stents and to elucidate the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%